Factors Associated with Mental Health Status of Pregnant Women - Eliyana Eliyana; Bambang Setiaji; Dian Utama Pratiwi Putri; Endang Budiati (GLOBAL HEALTH SCIENCE GROUP, 2026)
Mental health of pregnant women is an important aspect of efforts to improve the health status of mothers and children. South Lampung Regency still faces low achievement in mental health screening of pregnant women (22.27%). This study aims to determine the factors associated with the mental health status of pregnant women in South Lampung Regency in 2025. This study employed a quantitative approach with a cross-sectional analytical design. The study population consisted of all pregnant women attending nine selected community health centers in South Lampung Regency, with a total sample of 415 respondents selected using proportional random sampling. The dependent variable, namely the mental health status of pregnant women, was measured using the Edinburgh Postnatal Depression Scale (EPDS), which has been validated in the Indonesian population and demonstrated good reliability, with Cronbach’s alpha ranging from 0.78 to 0.85, indicating satisfactory internal consistency. A cut-off score of ≥10 was applied to classify pregnant women as being at risk of depression, as this threshold is considered sensitive for community-based screening in primary health care settings. The independent variables maternal age, gestational age, residence, spousal support, frequency of antenatal care (ANC) visits, and history of mental disorders were measured using a structured questionnaire. Data analysis was conducted using univariate, bivariate (Chi-Square test), and multivariate (multiple logistic regression) analyses. The results of the chi-square test showed a significant relationship between the age of the pregnant woman (p=0.000; OR=2.755), gestational age (p=0.014; OR=1.684), place of residence (p=0.004; OR=0.544), spousal support (p=0.000; OR=0.462), frequency of ANC visits (p=0.026; OR=0.625), and history of mental disorders (p=0.000; OR=3.595) with the mental health status of pregnant women. Multiple logistic regression analysis showed that the dominant factor associated with the mental health status of pregnant women was a history of mental disorders in the family (OR=4.453). In conclusion, there is a relationship between the age of pregnant women, gestational age, place of residence, spousal support, frequency of ANC visits, and history of mental disorders with the mental health status of pregnant women. The dominant influencing variable is a family history of mental disorders.